High Performance in Low Flow Solar Domestic Hot Water Systems - Dayan, Myrna (University of Wisconsin-Madison, 1997)
Low-flow solar hot water heating systems employ flow rates on the order of 1/5 to 1/10 of the conventional flow. Low-flow systems are of interest because the reduced flow rate allows smaller diameter tubing, which is less costly to install. Further, low-flow systems result in increased tank stratification. Lower collector inlet temperatures are achieved through stratification and the useful energy produced by the collector is increased. The disadvantage of low-flow systems is the collector heat removal factor, FR, decreases with decreasing flow rate. A serpentine collector has the potential to perform better than a conventional header-riser collector in low-flow systems due to the earlier onset of turbulent flow which enhances the internal heat transfer coefficient. The onset of turbulent flow is a function of the tube diameter and flow rate per tube. Many solar domestic hot water systems require an auxiliary electric source to operate a pump in order to circulate fluid through the solar collector. A photovoltaic driven pump can be used to replace the standard electrical pump. PV driven pumps provide an ideal means of controlling the flow rate, as pumps will only circulate fluid when there is sufficient radiation. The reduction of parasitic pumping power can also reduce on-peak utility demand. The PV pump, if adequately designed, decreases the system performance by a negligible amount. ii There has been some confusion as to whether optimum flow rates exist in a solar domestic hot water system utilizing a heat exchanger between the collector and the storage tank, as commonly employed for freeze protection. It was found that there exists thermal optimum or at least economical optimum flow rates when it is considered that low flow rates incur less hydraulic costs. Peak performance was always found to occur when the heat exchanger tank- side flow rate was approximately equal to the average load flow rate. For low collector-side flow rates, a small deviation from the optimum flow rate will dramatically effect system performance. However, system performance is insensitive to flow rate for high collector-side flow rates. Antifreeze solutions have temperature dependent properties such as density and specific heat. The effect of large temperature dependent property variations experienced by ethylene glycol and propylene glycol affect the optimum flow rate through the collector-side of the heat exchanger. The increased viscosity of the glycol at low temperatures impedes the onset of turbulence, which is detrimental to the heat exchanger UA.
Under the supervision of Professors William Beckman and Sanford Klein; 243pp.
Keywords: Thesis (M.S.)--University of Wisconsin--Madison, 1997.; Dissertations Academic Mechanical Engineering.; University of Wisconsin--Madison. College of Engineering.